Enhancement of boresight radiation for leaky wave antenna array - Mowafak K. Mohsen; M. S. M Isa; A. A. M. Isa; M. K. Abdulhameed; Mothana L. Attiah; Ahmed M. Dinar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
An array of half-width microstrip leaky-wave antennas (HW-MLWAs) of two uniform elements was designed to obtain maximum boresight radiation. Achieve this, two uniform of HW-MLWAs are placed at 180◦ and fed by a probe located at the center between the elements, two uniforms of HW-MLWAs, loaded terminated by 50Ω lumped element. Two beams from two branches individual merge to form the resultant directive beam. The simulation represents the susceptibility of the proposed array of uniform HW-MLWAs to the radiation broadside direction effectively. The predict bandwidth matched of the array is 582 MHz (4.18–4.76 GHz). The direction of its main beam in boresight happens over a wide 13%, relatively (4.18-4.76 GHz) band. The proposed peak gain at the boresight direction of the array is 9.91 dBi.